Cover Image, Volume 29, Issue 11. (November 2016) - Vandoorne, Katrien; Vandsburger, Moriel H.; Jacobs, I.; Han, Y.; Dafni, Hagit; Nicolay, Klaas; Strijkers, Gustav J.
Abstract : The cover image, by Katrien Vandoorne et al., is based on the Research Article Noninvasive mapping of endothelial dysfunction in myocardial ischemia by magnetic resonance imaging using an albumin‐based contrast agent, DOI:10.1002/nbm.3599 .